"Determinación del contenido de saponina y proteína en genotipos de quinua (Chenopodium quinua Willd) producidos en la finca experimental la María" - Coronel Rivera, Jeniffer Alexandra (2018)
The present research was carried out in the Laboratory of Bromatology of the Experimental La Maria Farm belonging to the Quevedo State Technical University located in the 7 ½ km of the Quevedo - El Empalme road, located in the province of Los Ríos. The overall objective was to determine the content of saponin and protein in quinua genotypes (Chenopodium quinoa Willd) produced at La Finca Experimental Farm. The experimental design was completely randomized with three replicates. For this, the following variables were evaluated: foam column height (cm), saponin content (%) and protein content (%) in quinoa seeds. The methodology used to obtain saponin content data was by the Koziol foaming method established in INEN Standard 1 672. The Kjeldahl method was used for protein. According to the evaluation it was found that most of the 30 genotypes evaluated belong to the bitter category, only six of them are sweet which corresponds to 20% of the total. While twenty-four genotypes are bitter being 80%. The protein content of the evaluated genotypes varies from 12.23 to 19.82%. In accordance with the provisions of the Codex Alimentarius, its acceptability being determined. Key words: Saponin, protein, Koziol, quinoa.